In-house green knowledge practice for hospital building maintenance - Mohammad Affendy, Omardin; Liu, Yao; Diyana, Kamarudin (2017)
The purpose of this study was to develop a knowledge practice model for the green hospital building maintenance. The proposed model was developed in a three-phase process: the information gathering phase using questionnaires, interviews and document analysis; the potential usefulness of the model was review on 8 BM managers. The results of the survey indicated that the model has the potential to improve the existing corrective and reactive maintenance management practices towards green maintenance practices. Well managing of the hospital building will be able to inspiration the quality of the hospital buildings that remain safe, long, and fine-looking and meet the standard without any harm and difficulties. Accordingly, this study will have highlighted the issues that impact in the hospital building occupancy as to develop the sustainable building value.